Breast cancer awareness among pharmacy and physiotherapy students of medical university Nawabshah - Rao Irfan; Hisbullah Memon; Ishfaque Nazeer Umrani; Habibullah Soomro (Journal of the Pakistan Medical Association, 2020)
Objective: To evaluate the knowledge and awareness of students at a medical university regarding possible risk factors and screening modalities of breast cancer. Methods: The cross-sectional study was conducted from January to April 2019 at the People’s University of Medical and Health Sciences for Women, Nawabshah, Pakistan, and compried young female students from first year to final year at the Institute of Pharmaceutical Sciences and the Institute of Physiotherapy and Rehabilitation Sciences of the university. Data was collected using a predesigned questionnaire, and was analysed using SPSS 21. Results: Of the 450 students approached, 375(84%) completed the questionnaire. The mean age of the participants was 21.06±1.164 years (range: 18-26 years). Overall, 225(60%) students said contraceptive pills could increase the risk of breast cancer, 267(71.2%) agreed that breast-feeding could reduce cancer risk, while 361 (96.27%) of the students had good mammography and clinical breast examination knowledge. Also, 308(82.13%) respondents knew about breast self-examination, but were not aware of its procedure. Conclusion: Majority of the subjects had knowledge and awareness about breast cancer, its risk factors, diagnostic parameters and possible treatment options, but they did not have knowledge regarding the procedures of breast self-examination. Key Words: Breast cancer, Risk factors, Mammography, Breast self-examination. Continuous...